Social Meaning' and 'Territory': epistemological approaches (Revista LIDER, 2020)
In this paper we make an epistemological analysis of 'Social Meaning' and 'Territory', concluding that the term territory refers to the construction which imaginatively created as prerequisite which a community will tend to materialize, according to the historical and social circumstances of the project and its ideal itinerary is created, or invented, according to how it is drawn, its emotion and utopia. In this sense, the territory is part of a collective dream in which its goals and values are materialized because it believes in them.